2016
DOI: 10.1021/jacs.6b00053
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Difluoromethylation of Aryl Halides via Base Metal Catalysis at Room Temperature

Abstract: A stable and isolable difluoromethyl zinc reagent has been prepared through the reaction of ICF2H with diethyl zinc and DMPU. This new zinc reagent is a free-flowing solid and can be used in combination with a nickel catalyst to difluoromethylate aryl iodides, bromides, and triflates at room temperature. Such mild conditions for the catalytic difluoromethylation of these substrates are unprecedented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
113
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(114 citation statements)
references
References 25 publications
0
113
0
1
Order By: Relevance
“…Currently, synthetic chemists pay great attention to the development of novel metal‐catalyzed difluoromethylation reactions . Nevertheless, these reactions rely on substitution of a halogen atom, a boronic acid, a triflyloxy group or diazonium salt with the difluoromethylated sources, respectively. The preparation of difluoromethylated compounds via silver‐catalyzed decarboxylation of α‐fluoroarylacetic acids, α,α‐difluoroarylacetic acids were also reported .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, synthetic chemists pay great attention to the development of novel metal‐catalyzed difluoromethylation reactions . Nevertheless, these reactions rely on substitution of a halogen atom, a boronic acid, a triflyloxy group or diazonium salt with the difluoromethylated sources, respectively. The preparation of difluoromethylated compounds via silver‐catalyzed decarboxylation of α‐fluoroarylacetic acids, α,α‐difluoroarylacetic acids were also reported .…”
Section: Methodsmentioning
confidence: 99%
“…A synthetic utility for these fluorinated zinc organometallics was introduced by reacting these reagents with diiodo(hetero)arenes under copper catalysis, producing fused fluorinated ring systems . Building up on these results, a dialkylzinc reagent, designed for difluoromethylation reactions, was developed . Thus, when difluoroiodomethane is treated with Et 2 Zn (0.5 equiv) in DMPU ( N , N ′‐dimethylpropyleneurea), the zinc reagent 133 is obtained in 94 % yield.…”
Section: Generation Of Fluorinated Organozinc Reagents By Halogen–zinmentioning
confidence: 99%
“…[8] In 2014, Shen reported the first catalytic difluoromethylation of aryl halides with TMSCF 2 H(2equiv), which proceeds at 80 8 8Cthrough cooperative palladium/silver catalysis(Scheme 1). [10] MacMillan reported the metallaphotoredox difluoromethylation of aryl bromides with bromodifluoromethane as ad irect source of CF 2 H radical through as ilyl radical-mediated halogen abstraction pathway. [10] MacMillan reported the metallaphotoredox difluoromethylation of aryl bromides with bromodifluoromethane as ad irect source of CF 2 H radical through as ilyl radical-mediated halogen abstraction pathway.…”
mentioning
confidence: 99%
“…Indeed, recent studies on decarbonylative cross-coupling reactions of carboxylic acid derivatives have demonstrated the viability of this approach for the construction of various types of C À Xb onds, [15][16][17][18] including examples such as decarbonylative Heck, [16] Suzuki, [17] and addition [18] reactions. [20] We began our investigations by studying the reaction of biaryl acid chloride 1a with (DMPU) 2 Zn(CF 2 H) 2 ,anucleophilic difluoromethylating reagent first reported by Vicic, [10] and found that ac atalyst system consisting of Pd(dba) 2 and RuPhos in 1,4-dioxane at room temperature provided the best results,affording 2a in 91 %isolated yield after 1hour.Upon closer examination, it was found that the acid chloride is completely consumed within 5minutes.T his outcome was unexpected as the available literature data on catalytic decarbonylative cross couplings unanimously indicated ar equirement for elevated temperatures and long reaction times.W eobserved astrong dependence of the reaction rate on the phosphine ligand, with bulky monodentate phosphines being key for an efficient transformation:e valuation of various ligands that have previously demonstrated effectiveness in Pd-catalyzed decarbonylative reactions did not show promising results in our reaction (Table 1, for details,see the Supporting Information ). Fore xample,i n2 017, Schoenebeck reported the first ever decarbonylative trifluoromethylation of acid fluorides,i n which they found that high temperature (at least 160 8 8C) is needed to overcome the barrier of the decarbonylation from an aroyl Pd II intermediate.…”
mentioning
confidence: 99%